Pengaruh Variabel Makroekonomi dan Volume Transaksi Saham Terhadap Harga Saham PT. Bumi Serpong Damai Tbk - Dhia Ulhaq Syafi Sauqi; Thomas Andrian; Tiara Nirmala; Nurbetty Herlina S.; Ukhti Ciptawaty (BULLET : Jurnal Multidisiplin Ilmu, 2023)
This study aims to analyze the effect of Gross Domestic Product (GDP), interest rate on deposits (SBD), transaction volume, and the Wholesale Price Index (IHBP) in the property sector on the stock price of PT. Bumi Serpong Damai Tbk (BSDE). The data used in this study are secondary data obtained monthly from January 2015 to December 2019 for PT Bumi Serpong Damai Tbk. The data processing method employed is Error Correction Model (ECM) analysis. The results of this study indicate that the GDP variable has a negative and insignificant effect on stock prices. However, in the long term, the GDP variable exhibits a significant negative effect on stock prices. The SBD variable shows a negative and significant effect on stock prices in both the short and long term. The transaction volume variable has a positive and significant effect on stock prices in both the short and long term. In the short term, the IHBP variable does not exhibit a significant positive effect. However, in the long term, the IHBP variable does not have a significant negative effect.